2003
DOI: 10.1291/hypres.26.789
|View full text |Cite
|
Sign up to set email alerts
|

Different Coronary Blood Flow Increase in Left Ventricular Hypertrophy Due to Hypertension Compared to Hypertrophic Cardiomyopathy at Elevated Heart Rate

Abstract: Coronary vasodilator reserve (CVR) is reduced in patients with left ventricular hypertrophy (LVH). However,it is not clear whether there is any difference between the coronary blood flow increase in LVH caused by hypertension (HTH) and that caused by hypertrophic cardiomyopathy (HCM) when the heart rate increases.In this study, 16 subjects with HTH, 10 subjects with HCM, and 10 subjects with normotension (NT) were investigated. Average peak velocities at rest, at pacing, and at dilatation were measured using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Total CBF in systemic arterial HTN was consistently found to be increased in studies using different methodologies to measure total CBF . Doppler assessment of blood flow in the LAD also showed an increased CBF in patients with HTN . Once the data were adjusted for LV mass, however, there was a significant reduction in CBF, a finding evident in the meta‐analysis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Total CBF in systemic arterial HTN was consistently found to be increased in studies using different methodologies to measure total CBF . Doppler assessment of blood flow in the LAD also showed an increased CBF in patients with HTN . Once the data were adjusted for LV mass, however, there was a significant reduction in CBF, a finding evident in the meta‐analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Eleven studies were identified and comprised the review of the effect of HTN on CBF in patients (Table ). Seven studies measured total blood flow and 4 measured flow in the left anterior descending coronary artery (LAD) . There were 318 persons with HTN and 185 controls.…”
Section: Resultsmentioning
confidence: 99%
“…A population of middle-aged to older males with HTN inevitably has a relatively high incidence of underlying CAD. The fact that endothelial function is so often abnormal in HTN patients (46,47) attests to the likelihood that sub-clinical CAD is common and may be the rule. Thus, while it certainly would be of great interest to perform similar measurements in a cohort without CAD, we believe that age and sex-matched control and HTN/concentric remodeling groups with a common background of CAD constitute a “real world” patient cohort that is also quite representative of those at risk for the development of HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…In each of the studies, mean CBF was increased in those with hypertension. The absolute value of CBF varied because some studies measured total myocardial blood flow [ 11 , 12 ] while others measured CBF in a single coronary artery [ 13 - 16 ]. In addition, techniques for CBF measurement varied widely.…”
Section: Resultsmentioning
confidence: 99%